National Leadership and Foreign Policy : A Case Study in the Mobilization of Public Support - Rosenau, James N. (Princeton, NJ : Princeton University Press, 2015)
An attempt to discover whether a foreign policy consensus can exist among the diverse groups in America, using data from 1,065 national leaders.Originally published in 1963.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- PART 1. Introduction -- CHAPTER I. National Leadership and Foreign Policy: A Derived Model -- CHAPTER II. National Leadership and Foreign Policy: An Empirical Wasteland -- CHAPTER III. National Leadership and Foreign Policy: A Case History -- PART II. The Conferees: A Profile of 647 Opinion-Makers -- CHAPTER IV. Social and Political Background -- CHAPTER V. Opinion-Making Outlets and Capacities -- CHAPTER VI. Involvement in Foreign Affairs -- CHAPTER VII. Foreign Aid Attitudes and Conceptions of the American People -- PART III. The Conference: Behavioral and Nonbehavioral Reactions -- CHAPTER VIII. Perceptions and Evaluations of the Conference -- CHAPTER IX. Post-Conference Activities: Opinion-Makers in Action -- PART IV. Summary and Speculation -- CHAPTER X. Consensus-Building in the American National Community -- Appendices -- APPENDIX A. The Questionnaire -- APPENDIX B. The Occupation Variable -- APPENDIX C. Derivation of the Index Scores -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Leadership -- Case studies; Public opinion -- United States; 2 -- isacsh